2011
DOI: 10.1007/s10800-011-0262-7
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical investigation of the roles of oxyanions in chemical–mechanical planarization of tantalum and tantalum nitride

Abstract: Nitrate, sulfate, and phosphate oxyanions are shown to serve as effective surface-modifying agents for low-pressure chemical-mechanical planarization (CMP) of Ta and TaN barrier layers of interconnect structures. The surface reactions that form the basis of this CMP strategy are investigated using cyclic voltammetry, open circuit potential and polarization resistance measurements, and impedance spectroscopy. The results suggest that forming structurally weak layers of surface oxides is crucial to chemically co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…For both Ru and Cu, a nearly linear correlation is observed between the values of i corr and those of the RRs measured in solutions I-III; this confirms the active roles of electrochemically promoted material removal in these specific cases. 60 On the other hand, for both Ru and Cu, the polish rates measured in solution IV fall outside the electrochemical correlation trends of the RRs with respect to i corr . This indicates that the chemical components of Ru-and Cu-CMP in solution IV are not strictly controlled by electrochemical steps.…”
Section: Corrosion Characteristics and Surface Reactions Ofmentioning
confidence: 83%
“…For both Ru and Cu, a nearly linear correlation is observed between the values of i corr and those of the RRs measured in solutions I-III; this confirms the active roles of electrochemically promoted material removal in these specific cases. 60 On the other hand, for both Ru and Cu, the polish rates measured in solution IV fall outside the electrochemical correlation trends of the RRs with respect to i corr . This indicates that the chemical components of Ru-and Cu-CMP in solution IV are not strictly controlled by electrochemical steps.…”
Section: Corrosion Characteristics and Surface Reactions Ofmentioning
confidence: 83%
“…15 It has also been shown that the carbonate/bicarbonate anions (contained in SPC) can serve as efficient surface modifiers of Cu and Ta to facilitate low pressure CMP of these metals. 16 Guanidine is broadly recognized for its surface complexing function in the contexts of Ru and Ta CMP. 4,17 The carbonate salt of guanidine is chosen here to match the anion component of the other complexing agent, SPC, used in the experimental slurry.…”
mentioning
confidence: 99%
“…The electrolytes, pHadjusted using HNO 3 , were prepared with reagent grade chemicals (Sigma Aldrich) and triply distilled water. Potentiodynamic and FT-EIS measurements were performed in a three-electrode glass cell of w100 ml volume, outfitted with a Pt counter electrode and a saturated calomel electrode (SCE) reference [25,26]. OCP transients were also recorded using this setup with the counter electrode disconnected.…”
Section: Methodsmentioning
confidence: 99%
“…If the electrode contains spatially discontinuous oxide films, such currents may not show a clear signature of surface passivation under moderate anodic activation. The surface oxides of Ta [25,26,30] and Al [46] formed here in the presence of the NO 3 À /AH À anions are in this category due to the known effects of anion-incorporation under such conditions [47]. Based on these considerations, the anodic component of i corr shown in Fig.…”
Section: Surface Modifying Roles Of Ascorbic Acid On Ta Co and Almentioning
confidence: 98%
See 1 more Smart Citation